2012
DOI: 10.1002/ptr.4649
|View full text |Cite
|
Sign up to set email alerts
|

Piperine Inhibits Lipopolysaccharide‐induced Maturation of Bone‐marrow‐derived Dendritic Cells Through Inhibition of ERK and JNK Activation

Abstract: Piperine, one of the main components of Piper longum Linn. and P. nigrum Linn., is a plant alkaloid with a long history of medicinal use. Piperine has been shown to modulate the immune response, but the mechanism underlying this modulation remains unknown. Here, we examined the effects of piperine on lipopolysaccharide (LPS)-induced inflammatory responses in bone-marrow-derived dendritic cells (BMDCs). Piperine significantly inhibited the expression of major histocompatibility complex class II, CD40 and CD86 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…It has been used as a medicinal herb for the treatment of rheumatoid arthritis in Japan, Korea, China and India (16). Piperine inhibited ERK and JNK pathways in dendritic cells, which supports its reputed use against some immune diseases such as arthritis and diabetes (17). It also possesses a broad-spectrum antimicrobial activity (18).…”
Section: Discussionmentioning
confidence: 87%
“…It has been used as a medicinal herb for the treatment of rheumatoid arthritis in Japan, Korea, China and India (16). Piperine inhibited ERK and JNK pathways in dendritic cells, which supports its reputed use against some immune diseases such as arthritis and diabetes (17). It also possesses a broad-spectrum antimicrobial activity (18).…”
Section: Discussionmentioning
confidence: 87%
“…The ability of piperine to inhibit inflammation has been attributed to a reduction in inflammatory mediator expression by macrophages in the presence of piperine Ying et al, 2013). However, piperine also inhibits lipopolysaccharide-induced maturation of dendritic cells, suggesting a decreased capacity to present antigen to T lymphocytes (Bae et al, 2012). In addition, piperine suppresses mouse T lymphocyte activation by mitogens (Dogra et al, 2004) and inhibits synthesis of Th2 cytokines in a mouse model of asthma (Kim and Lee, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Piper nigrum Linn. extract, piperine, significantly inhibited the maturation (MHC class II, CD40 and CD86), cytokine production (TNF-α and IL-12), phosphorylation of ERK and JNK, but enhanced the endocytosis activity of LPS-induced bone-marrow-derived DCs [32]. However, we did not observe significant alteration in the maturation markers of both conditions of treated mDCs.…”
Section: Discussionmentioning
confidence: 64%
“…The other plant components in AVS073 also have anti-inflammatory effect and analgesic activity [2430]. Some components of AVS073 showed direct anti-cancer properties through inhibiting cell growth or inducing cellular apoptosis, and indirect pathway via the immunological action of immune cells [31, 32]. Several in vitro and in vivo studies demonstrated that the extracts of AVS073′s components carried antioxidant, anti-inflammatory, immunomodulating and anti-cancer actions [3340].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation